Chemistry teacher and pre-service chemistry teacher views: Can social media be used as chemistry learning media? - Ari Syahidul Shidiq; Sri Yamtinah; Hayuni Retno Widarti (Pascasarjana Universitas Negeri Medan, 2023)
Chemistry learning should be able to integrate contextual chemistry problems and present the sophistication of 21st-century learning technology. As a product of 21st-century technology, social media can be used as chemistry learning media. Therefore, this study aims to investigate the views of chemistry teachers and pre-service chemistry teachers toward the potential use of social media as chemistry learning media. The Purposed-designed survey method that involved 76 chemistry teachers and 109 pre-service chemistry teachers as respondents was used in this study. A total of 40 question items were developed and distributed online using a Google form to respondents. Based on the results of the survey conducted, it is known that during online and offline chemistry learning, respondents are accustomed to using YouTube as chemistry learning media. In addition, Instagram is the social media most widely owned by pre-service chemistry teachers, while Facebook is the social media most commonly owned by chemistry teachers. Other results reveal that most respondents have the same screen time, more than 4 hours daily. This screen time is used by respondents for entertainment and looking for news information on social media. With this long screen time not used for learning, it can be a promising opportunity to use social media as chemistry learning media. This study is expected to be a reference for developing social media-based chemistry learning to increase student motivation and achievement.Keywords: Chemistry teacher; Learning media; Pre-service chemistry teacher; Social media; Views